PENGARUH PENGGUNAAN BUKU SEKOLAH ELEKTRONIK FISIKA DALAM PEMBELAJARAN TUNTAS TERHADAP PENCAPAIAN KOMPETENSI SISWA KELAS X SMA N 4 PADANG - Rahmi Hasynah (Universitas Negeri Padang, 2013)
This research aimed to investigate the effect of the use of electronic textbooks in teaching Physics to the achievement of student competencies completed. Type of research is quasi-experiment research. The population was students in class X SMA Negeri 4 Padang that is registered in academic years 2012/2013 Technique sampling this research is Purposive Sampling. The data obtained were analyzed using two similarity test average by t test. The results showed that the hypothesis which says